2016
DOI: 10.1137/15m1016369
|View full text |Cite
|
Sign up to set email alerts
|

Degeneracy in Finite Time of 1D Quasilinear Wave Equations

Abstract: We consider the large time behavior of solutions to the following nonlinear wave equation:is bounded away from a positive constant, we can construct a local solution for smooth initial data. However, if c(·) has a zero point, then c(u(t, x)) can be going to zero in finite time. When c(u(t, x)) is going to 0 in finite time, the equation degenerates. We give a sufficient condition that the equation with 0 ≤ λ < 2 degenerates in finite time. *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Specifically, he showed that all axially symmetric solutions (without any smallness assumption) lead to a finite-time degeneracy caused by the vanishing of a principal coefficient in the evolution equations. We also note that in the case of one spatial dimension, results similar to ours are obtained in [53,[95][96][97] using proofs by contradiction that rely on the method of Riemann invariants. However, since the method of Riemann invariants is not applicable in more than one spatial dimension and since we are interested in direct proofs, our approach here is quite different.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Specifically, he showed that all axially symmetric solutions (without any smallness assumption) lead to a finite-time degeneracy caused by the vanishing of a principal coefficient in the evolution equations. We also note that in the case of one spatial dimension, results similar to ours are obtained in [53,[95][96][97] using proofs by contradiction that rely on the method of Riemann invariants. However, since the method of Riemann invariants is not applicable in more than one spatial dimension and since we are interested in direct proofs, our approach here is quite different.…”
Section: Introductionsupporting
confidence: 74%
“…Speck would like to thank Yuusuke Sugiyama for bringing the references [53,[95][96][97] to his attention, to Michael Dreher for pointing out the references [70,71], to Willie Wong for pointing out the relevance of his work [99], and to an anonymous referee for pointing out the work [65].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…However, when p ′ goes to zero, the equations loss the strictly hyperbolicity. The author's papers [25,26] give a sufficient condition that the lack of the strictly hyperbolicity occurs in finite time. The p-system with γ < 1 would be meaningful in the study of elastic-plastic materials (e.g.…”
Section: Plan Of This Paper and Notationsmentioning
confidence: 99%
“…Johnson [7] and Yamaguchi and Nishida [23]). On the other hand, in [18,19] (see Remark 5 in [18] and Theorem 4.1 in [19]), the author has shown that the degeneracy (8) occurs in finite time, if…”
mentioning
confidence: 99%
“…The main theorem of this paper removes the compactness condition on initial data and extends the result in [8,17] to (1) with more general c(θ) and 0 ≤ λ < 2. In [17,18], the generalization on λ has already been pointed out without a proof. In fact, applying the method in [8,17] to the equation in (1), we can generalize the result in [17,18] to (1) with 0 ≤ λ < 2 and c(θ) = 1 + θ.…”
mentioning
confidence: 99%